Study in the optical performance of plastic scintillator with WLS fiber. (1st April 2023) - Lu, Peizhi; An, Fengpeng; Chen, Yu; Li, Min; Li, Yichen; Luo, Guang; Wang, Wei; Wang, Zhimin; Xiao, Xiang; Hor, Y.K.
Abstract: Muon veto is an important technique of many low background experiments. With the push in improving the sensitivity and statistics, the size of the detector for particle experiments has also been increasing. Therefore, there is a greater demand on the size of the muon veto system to efficiently identify muon events passing through the detector, minimizing the associated dead time of the target detector, and simultaneously fitting in the space requirements. In this paper, two designs of muon veto detectors composed of 200 cm×20 cm×2 cm plastic scintillator strip and a wavelength shifting(WLS) fiber coupled with SiPM, are tested. We use cosmic muons to examine the plastic scintillator along the length by scintillator cubes as probes and therefore measuring photoelectron numbers as a function of position. The design of layout-4 meets the needs of JUNO-TAO and is a compact and cheap candidate.